Predictors of atrial fibrillation detection in embolic stroke of undetermined source patients with implantable loop recorder - D’Anna, Lucio; La Cava, Roberta; Khetarpal, Ashni; Karjikar, Abeer; Almohtadi, Ahmad; Romoli, Michele; Foschi, Matteo; Ornello, Raffaele; De Santis, Federico; Sacco, Simona; Abu-Rumeileh, Samir; Lorenzut, Simone; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background. Covert atrial fibrillation (AF) is a predominant aetiology of embolic stroke of undetermined source (ESUS). Evidence suggested that AF is more frequently detected by implantable loop recorder (ILR) than by conventional monitoring. However, the predictive factors associated with occult AF detected using ILRs are not well established yet. In this study we aim to investigate the predictors of AF detection in patients with ESUS undergoing an ILR. Methods. This observational multi-centre study included consecutive ESUS patients who underwent ILR implantation. The infarcts were divided in deep, cortical infarcts or both. The infarction sites were categorized as anterior and middle cerebral artery, posterior cerebral artery with and without brainstem/cerebellum involvement. Multivariable logistic regression analysis was performed to investigate variables associated with AF detection. Results. Overall, 3000 patients were initially identified. However, in total, 127 patients who consecutively underwent ILR implantation were included in our analysis. AF was detected in 33 (26%) out of 127 patients. The median follow-up was 411 days. There were no significant differences in clinical characteristics and comorbidities between patients with and without AF detected. AF was detected more often after posterior cerebral artery infarct with brainstem/cerebellum involvement (p<0.001) whereas less often after infarction in the anterior and middle cerebral artery (p=0.021). Multivariable regression analysis demonstrated that posterior cerebral artery infarct with brainstem/cerebellum involvement was an independent predictor of AF detection. Conclusion. Our study showed that posterior circulation infarcts with brainstem/cerebellum involvement are associated with AF detection in ESUS patients undergoing ILR. Larger prospective studies are needed to validate our findings.